2015
DOI: 10.1021/acs.analchem.5b01594
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based RNA Extraction, in Situ Isothermal Amplification, and Lateral Flow Detection for Low-Cost, Rapid Diagnosis of Influenza A (H1N1) from Clinical Specimens

Abstract: The 2009 Influenza A (H1N1) pandemic disproportionately affected the developing world and high-lighted the key inadequacies of traditional diagnostic methods that make them unsuitable for use in resource-limited settings, from expensive equipment and infrastructure requirements to unacceptably long turnaround times. While rapid immunoassay diagnostic tests were much less costly and more context-appropriate, they suffered from drastically low sensitivities and high false negative rates. An accurate, sensitive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 25 publications
1
130
0
Order By: Relevance
“…Our group has previously reported on the successful isothermal amplification of nucleic acids within PES matrices 32 , as well as on the successful extraction of nucleic acids in PES followed by in situ amplification 14 . To test our HPV16 LAMP assay in situ , first we extracted solutions of known concentrations of HPV16 DNA mixed with our Glycoblue-containing lysis buffer through a PES membrane using an acrylic extraction setup previously described 14 . The extracted DNA was eluted from the PES matrices and quantified via qPCR (Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
“…Our group has previously reported on the successful isothermal amplification of nucleic acids within PES matrices 32 , as well as on the successful extraction of nucleic acids in PES followed by in situ amplification 14 . To test our HPV16 LAMP assay in situ , first we extracted solutions of known concentrations of HPV16 DNA mixed with our Glycoblue-containing lysis buffer through a PES membrane using an acrylic extraction setup previously described 14 . The extracted DNA was eluted from the PES matrices and quantified via qPCR (Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
“…A previous publication by Rohrman et al found that recombinase polymerase amplification (RPA) was also slightly inhibited when performed within cellulose matrix as compared to amplification in bound glass fibers (Rohrman and Richards-Kortum 2012). However, in detecting the H1N1 strain of Influenza A, we found no such inhibition of LAMP using porous polyethersulfone membranes (Rodriguez et al 2015). We began to question whether current paper-based diagnostic membranes were actually the most appropriate materials for in situ isothermal amplification in these point-of-care devices.…”
Section: Introductionmentioning
confidence: 83%
“…67 Rodriguez et al utilized streptavidin-biotin affinity to aggregate AgNPs and produce a colorimetric signal. 80 However, in the development of these methods it is important that the resulting aggregation is a response to only the analyte of interest and it is not a result of nonspecific aggregation.…”
Section: ·1 Optical and Fluorescence Based Detectionmentioning
confidence: 99%
“…97 Using paper modified with AuNPs, Rodriquez et al were able to extract, purify and detect Influenza A (H1N1) RNA. 80 Tsai et al detected tuberculosis using single strand DNA and AuNPs on a paper platform. 101 Zhang et al created a method of quantifying the number of white blood cells in human blood cells which can be used to assess the health of an individual.…”
Section: ·1 Clinical/medicinal Fieldmentioning
confidence: 99%